2016
DOI: 10.1155/2016/4146080
|View full text |Cite
|
Sign up to set email alerts
|

Pneumothorax Causing Pneumoperitoneum: Role of Surgical Intervention

Abstract: The most common cause of a pneumoperitoneum is a perforation of a hollow viscus and the treatment is an exploratory laparotomy; nevertheless, not all pneumoperitoneums are due to a perforation and not all of them need surgical intervention. We hereby present a case of pneumoperitoneum due to a diaphragmatic defect, which allowed air from a pneumothorax to escape through the diaphragmatic hernia into the abdominal cavity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…In most instances, Pneumothorax leading to the development of pneumoperitoneum is reported in the presence of a diaphragmatic hernia. 3,4 Likewise development of pneumothorax after laparoscopic surgeries where pneumoperitoneum is induced was also reported. 5 In up to 90% of the cases of pneumoperitoneum bowel perforation is the usual cause.…”
Section: Discussionmentioning
confidence: 91%
“…In most instances, Pneumothorax leading to the development of pneumoperitoneum is reported in the presence of a diaphragmatic hernia. 3,4 Likewise development of pneumothorax after laparoscopic surgeries where pneumoperitoneum is induced was also reported. 5 In up to 90% of the cases of pneumoperitoneum bowel perforation is the usual cause.…”
Section: Discussionmentioning
confidence: 91%
“…However, our patient presented some risk factors for pneumothorax, including sleep apnea apparatus syndrome and COPD treated with a long-acting anticholinergic agent. Duarte et al reported a case of pneumoperitoneum without digestive perforation related to a massive bilateral pneumothorax explained by diaphragmatic defect [4].…”
Section: Discussionmentioning
confidence: 99%
“…Pneumothorax associated with pneumoperitoneum is a rare event [3,4]. The link between the presence of intrapleural and intraperitoneal air without mediastinal communication has not been demonstrated to date without iatrogenic cause [3,4]. It is usually related to malformation or diaphragmatic trauma [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, only few cases have reported the concurrent manifestation of these two clinical entities in patients with specific diseases (ie, pleuroparenchymal fibroelastosis) or iatrogenic damages (ie, mechanical ventilation, gastro-esophageal anastomosis, aritificial pneumoperitoneum) [ 2 , [4] , [5] , [6] ].…”
Section: Introductionmentioning
confidence: 99%